(untitled) (Fiep Bulletin - online, 2013)
Among the many issues that permeate the context of teacher training, scientific research is presented as an opportunity for reflection of knowledge involving the profession, from the experiences of academics as researchers. In this sense aim to analyze the relevance of scientific research in the academic vision of Education Degree in Physics from the University of Santa Maria (UFSM) for their training. The approach used was the qualitative, with the current thinking of the phenomenology. The information-gathering instrument was a questionnaire answered by the third academic semester’s Degree in Physical Education UFSM. We show that these scholars have not sought comes in groups of studies and / or research in connection with the initial training, but already understand the relevance of such. In face of such evidence, it is essential invest more in basic scientific research in training courses for teachers, to learn about the benefits that it provides for future teachers, in that moving his thoughts to prepare them to cope and better understand the educational reality in which they enter